Evaluation of carotid artery Doppler measurements in late-onset fetal growth restriction: a cross-sectional study: Doppler measurements in fetal growth restriction - Kucukbas, Gokce Naz; Doğan, Yasemin (Journal of Surgery and Medicine, 2023)
Background/Aim: It has been reported that both the internal carotid artery (ICA) and the common carotid artery (CCA) are associated with hypoxia, also observed in late-onset fetal growth restriction (FGR). However, it has not yet been investigated whether these Doppler measurements differ in cases of late-onset FGR. This study evaluated the ICA and the CCA Doppler parameters in late-onset FGR fetuses and compared these measurements with those of healthy fetuses. Methods: This cross-sectional observational study comprised 75 singleton pregnancies diagnosed with late-onset FGR between the 32nd and 37th weeks of gestation, alongside 75 healthy fetuses paired 1:1 based on obstetric history and gestational age between June 2022 and May 2023. The Delphi consensus of 2016 was used for the definition of late-onset FGR. The exclusion criteria were congenital anomalies, presence of any additional disease, maternal body mass index over 35 kg/m2, abdominal scars hindering ultrasound visualization, use of medications such as antenatal steroids, sympathomimetics, and indomethacin that affect vascular function, drug use, smoking during pregnancy, concurrent preeclampsia, and multiple pregnancies. Upon the patients' admission to the hospital, their demographic characteristics were documented, and ultrasonographic examinations and Doppler measurements were subsequently performed. The Doppler velocimetry of the umbilical artery (UA) encompassed measurements of the systolic to diastolic ratio (S/D), pulsatility index (PI), and peak systolic velocity (PSV). The carotid artery Doppler velocimetry of the middle cerebral artery (MCA), ICA, and CCA encompassed measurements of the PI, resistance index (RI), and PSV. We assessed the diagnostic performance of Doppler measurements for late-onset FGR through receiver operating characteristic (ROC) analysis. Results: In the late-onset FGR group, the mean UA-SD was higher (2.7 [0.6] vs. 2.5 [0.5], P=0.006), and the mean UA-PI (0.8 [0.2] vs. 0.9 [0.2], P=0.011) and mean PSV (35.6 [8.2] vs. 41.1 [7.1], P<0.001) were lower compared to the control group. In the late-onset FGR group, carotid Doppler measurements were more pronounced than UA Doppler measurements. Moreover, ICA Doppler measurements exhibited superior diagnostic performance in predicting late-onset FGR compared to other Doppler measurements (Area under the curve [AUC]=0.777, P<0.001 for ICA-PI; AUC=0.751, P<0.001 for ICA-RI; AUC=0.749, P<0.001 for ICA-PSV). Conclusion: In fetuses with late-onset FGR, UA Doppler measurements showed minimal differences compared to healthy fetuses, but differences in carotid Doppler measurements, especially in the ICA, were more pronounced. Therefore, in the management of fetuses suspected of having late-onset FGR, a more detailed Doppler examination might be required.